Bilateral Facial Paralysis Caused by Bilateral Temporal Bone Fracture: A Case Report and a Literature Review - Sultan Şevik Eliçora; Aykut Erdem Dinç; Sultan Bişkin; Murat Damar; Ergin Bilgin (Case Reports in Otolaryngology)
Bilateral facial paralysis caused by bilateral temporal bone fracture is a rare clinical entity, with seven cases reported in the literature to date. In this paper, we describe a 40-year-old male patient with bilateral facial paralysis and hearing loss that developed after an occupational accident. On physical examination, House-Brackmann (HB) facial paralysis of grade 6 was observed on the right side and HB grade 5 paralysis on the left. Upon temporal bone computed tomography (CT) examination, a fracture line exhibiting transverse progression was observed in both petrous temporal bones. Our patient underwent transmastoid facial decompression surgery of the right ear. The patient refused a left-side operation. Such patients require extensive monitoring in intensive care units because the presence of multiple injuries means that facial functions are often very difficult to evaluate. Therefore, delays may ensue in both diagnosis and treatment of bilateral facial paralysis.